Modified isocyanate resin containing aggregation-induced emission group as well as preparation method and application of modified isocyanate resin

By introducing aggregation-induced light-emitting groups into isocyanate resins, modified isocyanate resins were prepared and combined with fluorocarbon resins. This solved the problem of low weather resistance of luminescent coatings in high temperature and high humidity environments, and achieved the stability and weather resistance of luminescent performance in high temperature and high humidity environments.

CN121449540APending Publication Date: 2026-02-03MARINE CHEM RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511559649.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-29
Publication Date
2026-02-03

AI Technical Summary

Technical Problem

Existing luminescent coatings containing aggregation-induced emission groups have low weather resistance in high temperature and high humidity environments, and external shear forces and pressures can damage the aggregation-induced emission groups, leading to a decrease or failure of luminescent performance.

Method used

A modified isocyanate resin was prepared by introducing tetraphenylethylene-isothiocyanate containing aggregation-induced light-emitting groups into 4,4'-dicyclohexylmethane diisocyanate using tromethamine, and then combined with fluorocarbon resin to prepare a luminescent weather-resistant coating.

Benefits of technology

To obtain coatings that combine luminescence properties and excellent weather resistance, remain stable in high temperature and high humidity environments, and do not fail under external pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_7
    Figure SMS_7
  • Figure SMS_10
    Figure SMS_10
  • Figure SMS_13
    Figure SMS_13
Patent Text Reader

Abstract

The invention relates to the technical field of luminescent coatings, in particular to modified isocyanate resin containing aggregation-induced emission groups as well as a preparation method and application of the modified isocyanate resin. According to the preparation method, tromethamine is adopted to introduce tetraphenyl ethylene-isothiocyanate containing an aggregation-induced emission group into 4, 4 '-dicyclohexylmethane diisocyanate, so that the modified isocyanate resin is obtained. Luminescent paint can be obtained by using the modified isocyanate resin as a curing agent. The fluorocarbon coating prepared by taking the modified isocyanate resin as a curing agent and matching the modified isocyanate resin with fluorocarbon resin has the advantages of luminescence property, excellent weather resistance and excellent stain resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of luminescent coating technology, and more specifically, to a modified isocyanate resin containing aggregation-induced luminescent groups, its preparation method, and its application. Background Technology

[0002] Fluorescent materials, as a type of photoluminescent material, can store energy after absorbing light from natural or artificial light sources, and then slowly release it as light. They offer advantages such as light storage and energy saving, and are widely used in various fields including building decoration, transportation, military, and fire protection. Products related to fluorescent materials include coatings, paints, ceramics, and plastics. Fluorescent coatings are one of the main applications of fluorescent materials, composed of fluorescent materials and organic compounds, and have a wide range of applications in the building decoration field.

[0003] Traditional fluorescent materials exhibit excellent luminescence performance in solution, but in the aggregated state, they often experience aggregation-induced fluorescence quenching, which reduces luminescence efficiency or even stops luminescence, limiting the application range of these materials. In 2001, Tang Benzhong et al. discovered that silole 1 does not emit light in solution but exhibits strong luminescence characteristics in the solid state, which they named aggregation-induced emission (AIE).

[0004] Aggregation-induced emission materials can solve the problem of aggregation fluorescence quenching. However, when used directly as coatings, their luminescent performance will decrease or fail in high-temperature and high-humidity environments. Incorporating aggregation-induced emission groups into resins or adding them directly to coatings will lead to a decrease in the weather resistance of the luminescent coatings. When using resins containing aggregation-induced emission groups to prepare coatings, high external shear forces and pressures will damage the aggregation-induced emission groups, resulting in a decrease or failure of the luminescent coating performance. Summary of the Invention

[0005] To address the technical problem of low weather resistance in existing luminescent coatings containing aggregation-induced emission groups, this invention provides a modified isocyanate resin containing aggregation-induced emission groups, its preparation method, and its application.

[0006] This invention utilizes tromethamine to introduce tetraphenylethylene-isothiocyanate containing aggregation-induced light-emitting groups onto 4,4'-dicyclohexylmethane diisocyanate, thereby obtaining a modified isocyanate resin. Using this modified isocyanate resin as a curing agent, luminescent coatings can be obtained. The fluorocarbon coating prepared by combining the modified isocyanate resin as a curing agent with a fluorocarbon resin exhibits both luminescent properties and excellent weather resistance, as well as superior stain resistance.

[0007] One of the objectives of this invention is to provide a modified isocyanate resin.

[0008] The modified isocyanate resin has the following structural formula: ; In the structural formula: R1 is R2 is .

[0009] The modified isocyanate resin is produced by reacting tromethamine, 4,4'-dicyclohexylmethane diisocyanate, and tetraphenylethylene-isothiocyanate.

[0010] Tetraphenylethylene-isothiocyanate was prepared using the method described in "Preparation and Application Performance of Chitosan Fluorescent Anti-counterfeiting Printing Coating" published by Li Manli et al. in the 2024 issue of the Journal of Textile Research, titled "Preparation Method of Tetraphenylethylene-Isothiocyanate".

[0011] A second objective of this invention is to provide a method for preparing the modified isocyanate resin described in one of the objectives of this invention.

[0012] The preparation method includes: grafting tromethamine with tetraphenylethylene-isothiocyanate in the presence of an organic solvent and a catalyst, and then polymerizing it with 4,4'-dicyclohexylmethane diisocyanate to obtain the modified isocyanate resin.

[0013] The organic solvent is selected from at least one of ester solvents, sulfone solvents, and benzene solvents, preferably from at least one of butyl acetate, dimethyl sulfoxide, benzene, toluene, and xylene, and more preferably from a mixture of dimethyl sulfoxide, xylene, and butyl acetate. When the organic solvent is a mixture of dimethyl sulfoxide, xylene, and butyl acetate, the ratio of the three can be any ratio, preferably a mixture of dimethyl sulfoxide, xylene, and butyl acetate in a weight ratio of 3:1:1.

[0014] The catalyst may be selected from at least one of dibutyltin dilaurate and stannous octoate.

[0015] The tromethamine is an active monomer containing 3 hydroxyl groups and 1 amino group, with the following structural formula: .

[0016] The tromethamine can be any one or more existing tromethamines. As a preferred option, the tromethamine can be selected from at least one of Xuzhou Maikai, Nantong Shenglun, and Hubei Kemaidi.

[0017] The chemical formula of the 4,4'-dicyclohexylmethane diisocyanate is OCN-R1-NCO, where R1 is... .

[0018] The chemical formula of the tetraphenylethylene-isothiocyanate is R2-CH2-CNS, where R2 is... .

[0019] The equation for the "grafting reaction of tromethamine with tetraphenylethylene-isothiocyanate" is as follows:

[0020] in, It is a product of the grafting reaction and is an intermediate product.

[0021] The phrase "then undergoing polymerization with 4,4'-dicyclohexylmethane diisocyanate" refers to the polymerization reaction between the grafting product and 4,4'-dicyclohexylmethane diisocyanate, with the following reaction equation: .

[0022] Based on the above reaction equation, it can be concluded that tromethamine, 4,4'-dicyclohexylmethane diisocyanate, and tetraphenylethylene-isothiocyanate react in a molar ratio of 1:3:1. Therefore, the molar ratio of tromethamine, 4,4'-dicyclohexylmethane diisocyanate, and tetraphenylethylene-isothiocyanate should be 1:3:1. To ensure the performance of the synthesized product, no substance should be in excess during the reaction. Unreacted 4,4'-dicyclohexylmethane diisocyanate will participate in the curing reaction, reducing the product's performance; unreacted tetraphenylethylene-isothiocyanate will react with 4,4'-dicyclohexylmethane diisocyanate, reducing the synthesis efficiency and affecting the product's performance; unreacted tromethamine will react with 4,4'-dicyclohexylmethane diisocyanate, reducing the synthesis efficiency and affecting the product's performance.

[0023] The preparation method, based on a total amount of 100 wt% of tromethamine, 4,4'-dicyclohexylmethane diisocyanate, tetraphenylethylene-isothiocyanate, organic solvent, and catalyst, comprises: 5-20 wt% organic solvent, preferably 9.2-15 wt%; 0.5-5 wt% catalyst, preferably 0.8-3.5 wt%; and the balance being tromethamine, 4,4'-dicyclohexylmethane diisocyanate, and tetraphenylethylene-isothiocyanate.

[0024] The preparation method, based on a total amount of 100 wt% of tromethamine, 4,4'-dicyclohexylmethane diisocyanate, tetraphenylethylene-isothiocyanate, organic solvent, and catalyst, uses an organic solvent of 5-20 wt%, for example, 8 wt%, 9 wt%, 10 wt%, 12 wt%, 15 wt%, 18 wt%, or any value between 5-20 wt% or any range between any two values, preferably 9.2-15 wt%.

[0025] The preparation method, based on a total amount of 100 wt% of tromethamine, 4,4'-dicyclohexylmethane diisocyanate, tetraphenylethylene-isothiocyanate, organic solvent and catalyst, uses a catalyst amount of 0.5-5 wt%, for example 1 wt%, 2 wt%, 3 wt%, 4 wt%, and any value or any range between 0.5-5 wt%, preferably 0.8-3.5 wt%.

[0026] The preparation method, based on a total amount of 100 wt% of tromethamine, 4,4'-dicyclohexylmethane diisocyanate, tetraphenylethylene-isothiocyanate, organic solvent, and catalyst, uses a sum of 80-95 wt% of tromethamine, 4,4'-dicyclohexylmethane diisocyanate, and tetraphenylethylene-isothiocyanate, for example 82 wt%, 85 wt%, 88 wt%, 90 wt%, 92 wt%, and any value between 80-95 wt% or any range between any two values, preferably 83-90 wt%.

[0027] The grafting reaction temperature can be 60-80℃, for example 65℃, 70℃, 75℃, preferably 67-75℃.

[0028] The grafting reaction can take 22-24 hours, for example, 23 or 24 hours.

[0029] The reaction temperature of the polymerization reaction can be 60-80℃, for example 65℃, 70℃, 75℃, preferably 67-75℃.

[0030] The reaction time for the polymerization reaction can be 4-6 hours, for example, 4.5 hours, 5 hours, or 5.5 hours.

[0031] One specific embodiment of the preparation method includes: mixing tromethamine with an organic solvent to form a liquid, then adding a catalyst and tetraphenylethylene-isothiocyanate to react at a temperature of 67-75°C for 22-24 hours; cooling to 40-45°C, then adding 4,4'-dicyclohexylmethane diisocyanate, raising the temperature to 67-75°C, reacting for 4-6 hours, and cooling to 40-45°C to obtain a low-viscosity solution containing modified isocyanate resin.

[0032] The low-viscosity solution containing the modified isocyanate resin or the modified isocyanate resin itself can be used directly as a curing agent for coatings.

[0033] The third objective of this invention is to provide a luminescent and weather-resistant coating.

[0034] The modified isocyanate resin prepared by the method described in either the first objective of the invention or the second objective of the invention, is used as a curing agent in the luminescent weather-resistant coating.

[0035] The luminescent weather-resistant coating, in one specific embodiment, includes component A and component B, wherein the mass ratio of component A to component B is (1-10):1, preferably (2-7):1; Component A contains fluorocarbon resin, pigments and fillers, additives, and diluent A; Component B contains modified isocyanate resin and diluent B.

[0036] The fluorocarbon resin can be any one or more existing fluorocarbon resins. As a preferred embodiment, the fluorocarbon resin can be selected from at least one of Dongfu Chemical ZHM-2, Asahi Glass LF-200, and Changxing Company 41011.

[0037] The pigments and fillers used in coatings can be any one or more. As a preferred option, the pigments and fillers can be selected from pigments with weather resistance and masking properties, such as titanium dioxide, carbon black, iron oxide red, medium chrome yellow, scarlet powder, phthalocyanine blue, phthalocyanine green, chromium oxide green, and ultraviolet phosphor, or functional pigments such as precipitated barium sulfate, talc, and mica powder; technicians can select according to the actual situation.

[0038] The additives can be any one or more conventional additives in the art. Preferably, they can be selected from at least one of defoamers, leveling agents, anti-settling agents, and wetting and dispersing agents. Specifically, the defoamer can be selected from at least one of BYK-066N type defoamer, BYK-054 type defoamer, AFCONA2720 type defoamer, and AFCONA2020 type defoamer; the leveling agent can be selected from at least one of BYK-331 type leveling agent, BYK-333 type leveling agent, AFCONA3700 type leveling agent, and AFCONA3770 type leveling agent; the anti-settling agent can be selected from at least one of fumed silica R972 and organobentonite CLAYMINTONE 75; and the wetting and dispersing agent can be selected from at least one of BYK-P104S type wetting and dispersing agent, BYK-163 type wetting and dispersing agent, and BYK-378 type wetting and dispersing agent.

[0039] The diluent A can be any one or more conventional diluents in the art. Preferably, diluent A is selected from at least one of ester solvents, sulfone solvents, and benzene solvents, more preferably from at least one of butyl acetate, dimethyl sulfoxide, benzene, toluene, and xylene, and more preferably from a mixture of dimethyl sulfoxide, xylene, and butyl acetate. When diluent A is a mixture of dimethyl sulfoxide, xylene, and butyl acetate, the ratio of the three can be any ratio, preferably a mixture of dimethyl sulfoxide, xylene, and butyl acetate in a 3:1:1 weight ratio.

[0040] The diluent B can be any one or more conventional diluents in the art. Preferably, the diluent B is selected from at least one of ester solvents, sulfone solvents, and benzene solvents, more preferably from at least one of butyl acetate, dimethyl sulfoxide, benzene, toluene, and xylene, and more preferably from a mixture of dimethyl sulfoxide, xylene, and butyl acetate. When the diluent B is a mixture of dimethyl sulfoxide, xylene, and butyl acetate, the ratio of the three can be any ratio, preferably a mixture of dimethyl sulfoxide, xylene, and butyl acetate in a 3:1:1 weight ratio.

[0041] The diluent A and diluent B may be the same or different.

[0042] Based on 100 parts by weight of fluorocarbon resin, the amount of modified isocyanate resin is 20-80 parts by weight, preferably 25-50 parts by weight.

[0043] The amounts of fluorocarbon resin, pigments and fillers, additives, diluent A, and diluent B can all be used in the usual amounts.

[0044] In one specific embodiment of the luminescent weather-resistant coating, the amounts of fluorocarbon resin, pigments and fillers, additives, diluent A, modified isocyanate resin, and diluent B are as follows: Based on 100 parts by weight of fluorocarbon resin: 100 parts by weight of fluorocarbon resin; Pigments and fillers: 20-100 parts by weight, preferably 25-80 parts by weight; Additives: 0.5-5 parts by weight, preferably 1-3 parts by weight; Diluent A: 50-90 parts by weight, preferably 54-87 parts by weight; 15-80 parts by weight of modified isocyanate resin, preferably 20-50 parts by weight; Diluent B is used in 5-50 parts by weight, preferably 10-40 parts by weight.

[0045] The fourth objective of this invention is to provide a method for preparing the luminescent weather-resistant coating described in the third objective of this invention.

[0046] The method for preparing the luminescent weather-resistant coating includes: mixing the components according to the specified weight proportions to obtain the luminescent weather-resistant coating.

[0047] The preparation method specifically includes the following steps: (1) Mix the fluorocarbon resin, pigments, fillers, additives and diluent A evenly according to the weight proportions, then grind them to 20-40 μm using a sand mill or three-roll mill, filter them through a filter screen to obtain component A; (2) Mix the modified isocyanate resin and diluent B evenly according to the weight parts to obtain the curing agent, i.e. component B; The luminescent weather-resistant coating is obtained by uniformly mixing components A and B according to their mass ratio.

[0048] The luminescent weather-resistant coating of the present invention can be applied by brushing or spraying; the coating thickness is controlled at 60-200μm to achieve the best performance.

[0049] Compared with the prior art, the beneficial effects of the present invention are as follows: The luminescent weather-resistant coating of the present invention has the following excellent comprehensive properties: Flexibility (mm): 1; Pull-off adhesion (MPa): 5.00 or higher; Impact strength (kg.cm): 50; Water resistance (23±2℃): No wrinkling, bubbles, or peeling of the paint film after 180 days; Abrasion resistance (weight loss / g at 500g and 500r): 0.06-0.12; Resistance to alternating damp heat and salt spray (salt spray (35℃×4h) + damp heat (50℃×7d)): The paint film does not crack, bubble, or peel after 4 cycles; Resistance to artificial weathering (UVB): Discoloration grade 0 after 3000 h, chalking grade 1, cracking grade 0; Salt spray resistance: No bubbling, peeling, or discoloration after 3000 hours; Stain resistance: Stain resistance level 1; Relative fluorescence intensity: 100%.

[0050] The luminescent weather-resistant coating of this invention can be cured at room temperature; it can be applied to protective coatings for sewage treatment ponds, swimming pools, water parks, dam embankments, bridge piers, stadium stands, roofs, balconies, terraces, high-speed railway subgrades and other building facilities, outdoor chemical equipment plants, offshore oil exploration drilling platforms, ship fenders and other protective fields that require long-term weather resistance and wear resistance. It can also be applied to instruments and equipment used at low temperatures, with the lowest temperature reaching -65℃. Detailed Implementation

[0051] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.

[0052] Except for tetraphenylethylene-isothiocyanate, all raw materials used in the examples and comparative examples are commercially available products.

[0053] The organic solvents used in the examples and comparative examples were: a mixture of dimethyl sulfoxide, xylene and butyl acetate, prepared in a ratio of 3:1:1 by weight. Diluent A in the examples and comparative examples is a mixture of dimethyl sulfoxide, xylene and butyl acetate, prepared in a ratio of 3:1:1 by weight. Diluent B in the examples and comparative examples is a mixture of dimethyl sulfoxide, xylene and butyl acetate, prepared in a ratio of 3:1:1 by weight.

[0054] Tetraphenylethylene-isothiocyanate was prepared using the method described in "Preparation and Application Performance of Chitosan Fluorescent Anti-counterfeiting Printing Coating" published by Li Manli et al. in the Journal of Textile Research in 2024.

[0055] Example 1 Preparation of modified isocyanate resins containing aggregation-induced light-emitting groups: 7.6 parts by weight (0.062 mol) of tromethamine (Xuzhou Maikai) was mixed with 15 parts by weight of organic solvent to form a liquid. Then, 2 parts by weight of dibutyltin dilaurate and 24.3 parts by weight (0.062 mol) of tetraphenylethylene-isothiocyanate were added. The mixture was reacted at 75°C for 22 hours, cooled to 45°C, and then 51.1 parts by weight (0.186 mol) of 4,4'-dicyclohexylmethane diisocyanate were added. The mixture was reacted at 75°C for 4 hours, cooled to 45°C, and discharged to obtain a low-viscosity solution of 83 wt% in 100 parts by weight. The low-viscosity solution contained organic solvent and the reaction product modified isocyanate resin, with the content of the reaction product modified isocyanate resin being 83 wt%.

[0056] Determination of low viscosity solutions using infrared absorption spectroscopy. The infrared absorption spectrum shows: in the 3400-3500 cm⁻¹ range... -1 The characteristic absorption peak of the hydroxyl group disappears, while the peak at 1730-1750 cm⁻¹ disappears. -1 and 1100-1150cm -1 The characteristic absorption peaks of ester bonds appear, and the product also shows absorption peaks in the 2260-2280 cm⁻¹ range. -1 The characteristic absorption peak of the NCO group did not disappear, remaining in the 1060-1250 cm⁻¹ range. -1 Characteristic absorption peaks of irregular vibrations of ether bonds appear; in the 3300-3400 cm⁻¹ range. -1 The characteristic absorption peak of the amino group disappears at 2000-2100 cm⁻¹. -1 The characteristic absorption peak of the isothiocyanate group disappears at 1130-1400 cm⁻¹, while the product's absorption peak at 1130-1400 cm⁻¹ disappears. -1 The characteristic absorption peak of thiourea appears at 900-1000 cm⁻¹. -1 The characteristic absorption peak of tetraphenylethylene appears at [location].

[0057] Infrared absorption spectroscopy confirms the structural formula of the reaction product modified isocyanate resin as follows:

[0058] R1 is R2 is .

[0059] Example 2 Preparation of modified isocyanate resins containing aggregation-induced light-emitting groups: Eight parts by weight (0.066 mol) of tromethamine (Nantong Shenglun) were mixed with 9.2 parts by weight of organic solvent to form a liquid. Then, 0.8 parts by weight of stannous octoate and 26 parts by weight (0.066 mol) of tetraphenylethylene-isothiocyanate were added. The mixture was reacted at 67°C for 24 hours, cooled to 40°C, and then 56 parts by weight (0.198 mol) of 4,4'-dicyclohexylmethane diisocyanate were added. The mixture was reacted at 67°C for 6 hours, cooled to 40°C, and discharged to obtain a 90 wt% low-viscosity solution in 100 parts by weight. The low-viscosity solution contained the organic solvent and the reaction product modified isocyanate resin, with the content of the reaction product modified isocyanate resin being 90 wt%.

[0060] Determination of low viscosity solutions using infrared absorption spectroscopy. The infrared absorption spectrum shows: in the 3400-3500 cm⁻¹ range... -1 The characteristic absorption peak of the hydroxyl group disappears, while the peak at 1730-1750 cm⁻¹ disappears. -1 and 1100-1150cm -1 The characteristic absorption peaks of ester bonds appear, and the product also shows absorption peaks in the 2260-2280 cm⁻¹ range. -1 The characteristic absorption peak of the NCO group did not disappear, remaining in the 1060-1250 cm⁻¹ range. -1 Characteristic absorption peaks of irregular vibrations of ether bonds appear; in the 3300-3400 cm⁻¹ range. -1 The characteristic absorption peak of the amino group disappears at 2000-2100 cm⁻¹. -1 The characteristic absorption peak of the isothiocyanate group disappears at 1130-1400 cm⁻¹, while the product's absorption peak at 1130-1400 cm⁻¹ disappears. -1 The characteristic absorption peak of thiourea appears at 900-1000 cm⁻¹. -1 The characteristic absorption peak of tetraphenylethylene appears at [location].

[0061] Infrared absorption spectroscopy confirms the structural formula of the reaction product modified isocyanate resin as follows:

[0062] R1 is R2 is .

[0063] Example 3 Preparation of modified isocyanate resins containing aggregation-induced light-emitting groups: 6.9 parts by weight (0.057 mol) of tromethamine (Hubei Kemaidi) was mixed with 9.5 parts by weight of organic solvent to form a liquid. Then, 3.5 parts by weight of dibutyltin dilaurate and 25.31 parts by weight (0.057 mol) of tetraphenylethylene-isothiocyanate were added. The mixture was reacted at 70°C for 23 hours, cooled to 42°C, and then 54.79 parts by weight (0.171 mol) of 4,4'-dicyclohexylmethane diisocyanate were added. The mixture was reacted at 70°C for 5 hours, cooled to 42°C, and discharged to obtain a low-viscosity solution of 87 wt% (100 parts by weight). The low-viscosity solution contained organic solvent and the reaction product modified isocyanate resin, with the content of the reaction product modified isocyanate resin being 87 wt%.

[0064] Determination of low viscosity solutions using infrared absorption spectroscopy. The infrared absorption spectrum shows: in the 3400-3500 cm⁻¹ range... -1 The characteristic absorption peak of the hydroxyl group disappears, while the peak at 1730-1750 cm⁻¹ disappears. -1 and 1100-1150cm -1 The characteristic absorption peaks of ester bonds appear, and the product also shows absorption peaks in the 2260-2280 cm⁻¹ range. -1 The characteristic absorption peak of the NCO group did not disappear, remaining in the 1060-1250 cm⁻¹ range. -1 Characteristic absorption peaks of irregular vibrations of ether bonds appear; in the 3300-3400 cm⁻¹ range. -1 The characteristic absorption peak of the amino group disappears at 2000-2100 cm⁻¹. -1 The characteristic absorption peak of the isothiocyanate group disappears at 1130-1400 cm⁻¹, while the product's absorption peak at 1130-1400 cm⁻¹ disappears. -1 The characteristic absorption peak of thiourea appears at 900-1000 cm⁻¹. -1 The characteristic absorption peak of tetraphenylethylene appears at [location].

[0065] Infrared absorption spectroscopy confirms the structural formula of the reaction product modified isocyanate resin as follows:

[0066] R1 is R2 is .

[0067] Example 4 Preparation of luminescent weather-resistant coatings: Weigh 100 parts by weight of fluorocarbon resin (Dongfu Chemical ZHM-2), put it into a stainless steel tank and stir with a high-speed mixer. Add 0.1 parts by weight of defoamer BYK066N, 0.1 parts by weight of leveling agent BYK331, 0.3 parts by weight of anti-settling agent fumed silica R972, and 0.5 parts by weight of wetting and dispersing agent BYK-P104S. After stirring evenly, add 2 parts by weight of carbon black, 18 parts by weight of titanium dioxide, 1 part by weight of medium chrome yellow, 1 part by weight of scarlet powder, 1 part by weight of phthalocyanine blue, 1 part by weight of talc powder, 1 part by weight of mica powder, and 54 parts by weight of diluent A and stir evenly. Then grind it to the standard fineness using a sand mill or three-roll mill, filter and package it as coating component A.

[0068] Weigh 50 parts by weight of the modified isocyanate resin prepared in Example 1 and mix 40 parts by weight of diluent B evenly to form component B of the coating.

[0069] When using, mix components A and B at a weight ratio of 2:1 and then spray them into a film.

[0070] Example 5 Preparation of luminescent weather-resistant coatings: Weigh 100 parts by weight of fluorocarbon resin (Asahi Glass LF200), put it into a stainless steel tank and stir with a high-speed mixer. Add 0.3 parts by weight of defoamer BYK054, 0.3 parts by weight of leveling agent AFCONA3700, 1 part by weight of anti-settling agent fumed silica R972, and 1.4 parts by weight of wetting and dispersing agent BYK-163. After stirring evenly, add 32 parts by weight of titanium dioxide, 20 parts by weight of iron oxide red, 6 parts by weight of medium chrome yellow, 10 parts by weight of phthalocyanine green, 6 parts by weight of precipitated barium sulfate, 6 parts by weight of talc, and 87 parts by weight of diluent A. Stir evenly, then grind to standard fineness using a sand mill or three-roll mill. Filter and package as coating component A.

[0071] Weigh 25 parts by weight of the modified isocyanate resin prepared in Example 3 and mix 20 parts by weight of diluent B until homogeneous. This is component B of the coating.

[0072] When using, mix components A and B at a weight ratio of 6:1 and then spray them into a film.

[0073] Example 6 Preparation of luminescent weather-resistant coatings: Weigh 100 parts by weight of fluorocarbon resin (Changxing 41011), put it into a stainless steel tank and stir with a high-speed mixer. Add 0.3 parts by weight of defoamer AFCONA2720, 0.3 parts by weight of leveling agent BYK333, 751 parts by weight of anti-settling agent organic bentonite CLAYMINTONE, and 1.2 parts by weight of wetting and dispersing agent BYK-378. After stirring evenly, add 15 parts by weight of titanium dioxide, 8 parts by weight of iron oxide red, 5 parts by weight of red powder, 4.2 parts by weight of chromium oxide green, 5 parts by weight of precipitated barium sulfate, 7 parts by weight of mica powder, and 63 parts by weight of diluent A. Stir evenly, then grind to standard fineness using a sand mill or three-roll mill. Filter and package as coating component A.

[0074] Weigh 20 parts by weight of the modified isocyanate resin prepared in Example 3 and mix 10 parts by weight of diluent B until homogeneous. This is component B of the coating.

[0075] When using, mix components A and B at a weight ratio of 7:1 and then spray them into a film.

[0076] Example 7 Preparation of luminescent weather-resistant coatings: Weigh 100 parts by weight of fluorocarbon resin (Dongfu Chemical ZHM-2), put it into a stainless steel tank and stir with a high-speed mixer. Add 0.2 parts by weight of defoamer AFCONA2020, 0.1 parts by weight of leveling agent AFCONA3770, 0.7 parts by weight of anti-settling agent organic bentonite CLAYMINTONE75, and 1 part by weight of wetting and dispersing agent BYK-163. After stirring evenly, add 25 parts by weight of titanium dioxide, 2 parts by weight of carbon black, 10 parts by weight of medium chrome yellow, 10 parts by weight of phthalocyanine blue, 3 parts by weight of precipitated barium sulfate, 3 parts by weight of talc powder, 10 parts by weight of mica powder, and 75 parts by weight of diluent A. Stir evenly, then grind to standard fineness using a sand mill or three-roll mill. Filter and package as coating component A.

[0077] Weigh 35 parts by weight of the modified isocyanate resin prepared in Example 2 and mix 25 parts by weight of diluent B until homogeneous. This is component B of the coating.

[0078] When using, mix components A and B at a weight ratio of 4:1 and then spray them into a film.

[0079] Comparative Example 1 Preparation of weather-resistant coatings: Weigh 100 parts by weight of fluorocarbon resin (Dongfu Chemical ZHM-2), put it into a stainless steel tank and stir with a high-speed mixer. Add 0.1 parts by weight of defoamer BYK066N, 0.1 parts by weight of leveling agent BYK331, 0.3 parts by weight of anti-settling agent fumed silica R972, and 0.5 parts by weight of wetting and dispersing agent BYK-P104S. After stirring evenly, add 2 parts by weight of carbon black, 18 parts by weight of titanium dioxide, 1 part by weight of medium chrome yellow, 1 part by weight of scarlet powder, 1 part by weight of phthalocyanine blue, 1 part by weight of talc powder, 1 part by weight of mica powder, and 54 parts by weight of diluent A and stir evenly. Then grind it to the standard fineness using a sand mill or three-roll mill, filter and package it as coating component A.

[0080] Weigh 24 parts by weight of Bayer N3390 isocyanate resin (excluding aggregation-induced light-emitting groups) and 12 parts by weight of diluent B, and stir evenly to form component B of the coating.

[0081] When using, mix components A and B at a weight ratio of 5:1 and then spray them into a film.

[0082] Comparative Example 2 Preparation of weather-resistant coatings: Weigh 100 parts by weight of fluorocarbon resin (Dongfu Chemical ZHM-2), put it into a stainless steel tank and stir with a high-speed mixer. Add 0.1 parts by weight of defoamer BYK066N, 0.1 parts by weight of leveling agent BYK331, 0.3 parts by weight of anti-settling agent fumed silica R972, and 0.5 parts by weight of wetting and dispersing agent BYK-P104S. After stirring evenly, add 2 parts by weight of carbon black, 17 parts by weight of titanium dioxide, 1 part by weight of medium chrome yellow, 1 part by weight of scarlet powder, 1 part by weight of phthalocyanine blue, 1 part by weight of talc powder, 1 part by weight of mica powder, and 54 parts by weight of diluent A and stir evenly. Then grind it to the standard fineness using a sand mill or three-roll mill. After filtering, add 1 part by weight of aggregation-induced luminescence material (ultraviolet phosphor), stir evenly, and package it as coating component A.

[0083] Weigh 24 parts by weight of Bayer N3390 isocyanate resin (excluding aggregation-induced light-emitting groups) and 12 parts by weight of diluent B, and stir evenly to form component B of the coating.

[0084] When using, mix components A and B at a weight ratio of 5:1 and then spray them into a film.

[0085] Performance testing The coatings obtained in Examples 4-7 and Comparative Examples 1-2 were sprayed into films (film thickness is specified in the following test standards. In the tests, the coatings were prepared according to the standard requirements). The properties of the resulting coatings were then tested.

[0086] The flexibility was determined according to GB / T1731 Test Method for Flexibility of Coating Film; The pull-off adhesion was tested according to GB / T5210 Paint and Varnish Pull-off Adhesion Test. Impact strength was determined according to GB / T1732 Test Method for Impact Resistance of Paint Film; water resistance was determined according to GB / T9274 Test Method for Resistance of Paints and Varnishes to Liquid Media. Resistance to alternating damp heat salt spray was tested according to CB 1146.13 Environmental Test Method for Marine Equipment: alternating salt spray was measured under the following conditions: salt spray (35℃×4h) + damp heat (50℃×7d). The artificial weathering resistance (UVB) was determined according to GB / T 14522 Test method for artificial weathering of plastics, coatings and rubber materials for mechanical industry products and GB / T 1766 Rating method for aging of paint and varnish coatings under fluorescent ultraviolet lamps. Salt spray resistance was determined according to GB / T1771 Test of neutral salt spray resistance of paints and varnishes; The stain resistance was determined according to GB / T9780 Test Method for Stain Resistance of Architectural Coatings. The relative fluorescence brightness was determined according to GB / T17001.1 Anti-counterfeiting inks Part 1: Ultraviolet-excited fluorescent anti-counterfeiting inks; The test results are shown in Table 1.

[0087] Table 1

[0088] In Table 1, resistance to artificial weathering (UVB) characterizes weather resistance.

[0089] Examples 4-7 exhibit excellent luminescent properties, as well as superior flexibility, pull-out adhesion, impact strength, water resistance, resistance to alternating damp heat and salt spray, resistance to artificial weathering (UVB), salt spray resistance, and stain resistance.

[0090] Compared to Comparative Example 1, Comparative Example 2 exhibits superior luminescence properties; however, its resistance to artificial weathering (UVB) is significantly lower than that of Comparative Example 1. The only difference between Comparative Example 2 and Comparative Example 1 is the introduction of aggregation-induced emission groups: Comparative Example 1 did not introduce aggregation-induced emission groups, while Comparative Example 2 introduced aggregation-induced emission groups into component A based on Comparative Example 1. It is evident that "introducing aggregation-induced emission groups into component A" can endow the coating with luminescence properties, but it leads to a decrease in the coating's weather resistance.

[0091] Compared to Comparative Example 1, Example 4 exhibits superior luminescent properties. Furthermore, the flexibility, pull-off adhesion, impact strength, water resistance, resistance to alternating humid heat and salt spray, resistance to artificial weathering (UVB), salt spray resistance, and stain resistance of Example 4 are comparable to those of Comparative Example 1. The only difference between Example 4 and Comparative Example 1 is the introduction of aggregation-induced light-emitting groups: Example 4 introduced aggregation-induced light-emitting groups (using a modified isocyanate resin containing aggregation-induced light-emitting groups as a curing agent), while Comparative Example 1 did not introduce aggregation-induced light-emitting groups. Therefore, by introducing aggregation-induced light-emitting groups using the method of this invention, the coating can possess luminescent properties while ensuring that its flexibility, pull-off adhesion, impact strength, water resistance, resistance to alternating humid heat and salt spray, resistance to artificial weathering (UVB), salt spray resistance, and stain resistance are not diminished.

[0092] The UVB resistance of Comparative Example 2 was lower than that of Example 4. The only difference between Example 4 and Comparative Example 2 was the method of introducing the aggregation-induced light-emitting group: Comparative Example 2 directly introduced the aggregation-induced light-emitting group into component A; Example 4 first modified the isocyanate resin with the aggregation-induced light-emitting group, and then used the modified isocyanate resin as a curing agent. It is evident that, compared to the method of introducing the aggregation-induced light-emitting group in Comparative Example 2, the method of introducing the aggregation-induced light-emitting group in this invention can enable the coating to possess luminescent properties while ensuring that the coating's weather resistance does not decrease, thus solving the technical problem of "integrating the aggregation-induced light-emitting group into the resin, leading to a decrease in the weather resistance of the luminescent coating."

Claims

1. A modified isocyanate resin, having the following structural formula: ; R1 is ; R2 is .

2. The modified isocyanate resin according to claim 1, characterized in that, It is produced by the reaction of tromethamine, 4,4'-dicyclohexylmethane diisocyanate, and tetraphenylethylene-isothiocyanate.

3. A method for preparing the modified isocyanate resin according to claim 1 or 2, comprising: In the presence of an organic solvent and a catalyst, tromethamine is grafted onto tetraphenylethylene-isothiocyanate, and then polymerized with 4,4'-dicyclohexylmethane diisocyanate to obtain the modified isocyanate resin.

4. The preparation method according to claim 3, characterized in that, The organic solvent is selected from at least one of ester solvents, sulfone solvents, and benzene solvents, preferably from at least one of butyl acetate, dimethyl sulfoxide, benzene, toluene, and xylene, more preferably from a mixture of dimethyl sulfoxide, xylene, and butyl acetate; or / and, The catalyst is selected from at least one of dibutyltin dilaurate and stannous octoate.

5. The preparation method according to claim 3, characterized in that, Based on a total of 100 wt% of tromethamine, 4,4'-dicyclohexylmethane diisocyanate, tetraphenylethylene-isothiocyanate, organic solvents, and catalysts: The amount of organic solvent used is 5-20 wt%, preferably 9.2-15 wt%; The amount of catalyst used is 0.5-5 wt%, preferably 0.8-3.5 wt%.

6. The preparation method according to claim 3, characterized in that, The grafting reaction temperature is 60-80℃, preferably 67-75℃; or / and, The grafting reaction time is 22-24 hours; or / and, The polymerization reaction temperature is 60-80℃, preferably 67-75℃; or / and, The polymerization reaction time is 4-6 hours.

7. A luminescent weather-resistant coating, wherein the modified isocyanate resin as described in claim 1 or 2, or the modified isocyanate resin prepared by any one of the preparation methods described in claims 3-6, is used as a curing agent.

8. The luminescent weather-resistant coating as described in claim 7, characterized in that, It includes component A and component B, with the mass ratio of component A to component B being (1-10):1, preferably (2-7):1; Component A contains fluorocarbon resin, pigments and fillers, additives, and diluent A; Component B contains modified isocyanate resin and diluent B.

9. The luminescent weather-resistant coating as described in claim 8, characterized in that, Based on 100 parts by weight of fluorocarbon resin: 100 parts by weight of fluorocarbon resin; Pigments and fillers: 20-100 parts by weight, preferably 25-80 parts by weight; Additives: 0.5-5 parts by weight, preferably 1-3 parts by weight; Diluent A: 50-90 parts by weight, preferably 54-87 parts by weight; 15-80 parts by weight of modified isocyanate resin, preferably 20-50 parts by weight; Diluent B is used in 5-50 parts by weight, preferably 10-40 parts by weight.

10. A method for preparing the luminescent weather-resistant coating as described in any one of claims 7-9 comprises: The components are mixed in the specified weight proportions to obtain the luminescent weather-resistant coating.